KANBAN allocation in a serial suply chain - Sánchez C., Guillermo Andrés; Sanchez C., Juan Manuel; Patiño H., Oscar Huberto (Tecnura, 2012)
The aim of this project is to simulate a Kanban system using N stages with the objective of maintaining an acceptable throughput and mean system time. The document shows the production systems where Kanban is applicable and what the potential benefi ts are. A serial of simulations will be done using a demand given by a poison distribution with rate λ ^ ext. The simulation aimed to fi nd the best number of withdrawal Kanban on all N stages when the values of μ (for exponential distribution of the process) and λ ^ ext increase and decrease. At the end of this simulation, the best way to allocate the withdrawal Kanban over N stages with the objective of maintaining acceptable throughput and mean system time will be clearer thus the conclusions of this work will be done.